2016
DOI: 10.1074/jbc.m116.715698
|View full text |Cite
|
Sign up to set email alerts
|

RNF8 E3 Ubiquitin Ligase Stimulates Ubc13 E2 Conjugating Activity That Is Essential for DNA Double Strand Break Signaling and BRCA1 Tumor Suppressor Recruitment

Abstract: DNA double strand break (DSB) responses depend on the sequential actions of the E3 ubiquitin ligases RNF8 and RNF168 plus E2 ubiquitin-conjugating enzyme Ubc13 to specifically generate histone Lys-63-linked ubiquitin chains in DSB signaling. Here, we defined the activated RNF8-Ubc13∼ubiquitin complex by x-ray crystallography and its functional solution conformations by x-ray scattering, as tested by separation-of-function mutations imaged in cells by immunofluorescence. The collective results show that the RIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 65 publications
0
45
0
Order By: Relevance
“…Within chromatin DNA is protected from damage but also restricted from repair, so the interactions of DDR in chromatin will be of central importance going forward. Based upon current results, we can expect multiple PTMs including ubiquitin and SUMO-ylation to act in switching conformations and interactions to coordinate repair in chromatin (e.g., Groocock et al, 2014; Hodge et al, 2016). …”
Section: What’s Aheadmentioning
confidence: 62%
“…Within chromatin DNA is protected from damage but also restricted from repair, so the interactions of DDR in chromatin will be of central importance going forward. Based upon current results, we can expect multiple PTMs including ubiquitin and SUMO-ylation to act in switching conformations and interactions to coordinate repair in chromatin (e.g., Groocock et al, 2014; Hodge et al, 2016). …”
Section: What’s Aheadmentioning
confidence: 62%
“…The ubiquitin ligase activity of BRCA1 has been reported to contribute to its DNA damage repair function [2830] We compared HCC1937 cells which exhibit a severe deficit in BRCA1-mediated DNA repair, [31, 32] with cells that were rescued with full length BRCA1 (HCC1937+WT) or transfected with a full-length, point-mutated form of BRCA1 which lacks its ubiquitin ligase activity (HCC1937+I26A) (Fig 6). We found that T575 phosphorylation of G1 cells was significantly higher in HCC1937 cells compared to those that had been transfected with full length WT BRCA1 (HCC1937+WT; p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…(a) Ribbon representation of a single RNF4 monomer from UBE2D1~Ub:RNF4 complex (PDB: 4AP4) showing the zinc ions as spheres, the residues involved in zinc‐coordination and the allosteric linchpin residue as ball‐and‐sticks, and demarcating the E2‐binding site. The ribbon diagram is colored to reflect the average pairwise positional shift of each overlapping C α atom between RNF4 and unique RING cores from all available E2–RING E3 complex structures including RNF146 (PDB: 4QPL), TRIM25 (PDB: 5FER), BIRC2 (PDB: 6HPR), BIRC3 (PDB: 3 EB6), BIRC7 (PDB: 4AUQ), RNF38 (PDB: 4V3K), RNF25 (PDB: 5D1M), RNF165 (PDB: 5D0M), MDM2 (PDB: 5MNJ), TRIM23 (PDB: 5VZW), RNF13 (PDB: 5ZBU), E4B (PDB: 3L1Z), RNF2 (PDB: 3RPG), GP78 (PDB: 2LXP), SIZ1 (PDB: 5JNE), c‐CBL (PDB: 1FBV), RBX1 (PDB: 4P5O), TRAF6 (PDB: 3HCT), TRIM5 (PDB: 4TKP), RNF8 (PDB: 4WHV), ZNRF1 (PDB: 5YWR), LNX1 (PDB: 5H7S), CHIP (PDB: 2C2V), and FANCL (PDB: 2CCG) . (b) UBE2D1~Ub:RNF4 complex highlighting position of the RING domain relative to the E2, with the allosteric linchpin residue coordinating E2 as well as the donor Ub shown as ball‐and‐sticks.…”
Section: Ring E3 Morphologymentioning
confidence: 99%
“…Nevertheless, variations are tolerated. For example, the cCBL‐UBE2L3 and RNF8‐UBE2N complexes lack one of the salt bridges and the stacking van der Waals interaction that tether the E2 α1 to RING E3 ZI A . In contrast, some RINGs such as TRIM23, RNF13, RNF2, and Glycoprotein 78 (GP78) have a carboxylate‐containing residue on their ZI A and form an additional salt bridge with E2 α1 (Figure S3).…”
Section: The Canonical E2–ring E3 Interactionmentioning
confidence: 99%